Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c7ta05131j
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon nitride (g-C3N4)-based photocatalysts for solar hydrogen generation: recent advances and future development directions

Abstract: Analyzing the commercialization potential of g-C3N4photocatalysts for solar H2generation from an economic viewpoint and for large-scale production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
212
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(232 citation statements)
references
References 239 publications
1
212
0
1
Order By: Relevance
“…
has become a star in water splitting [3][4][5][6][7] and CO 2 reduction. [8][9][10] Although many studies have been widely carried out, its CO 2 reduction performance is still far from the actual application requirements and the product is mainly CO (2-electron reduction product), [11,12] due to the high recombination rate of charge carriers and low reaction dynamics.
…”
mentioning
confidence: 99%
“…
has become a star in water splitting [3][4][5][6][7] and CO 2 reduction. [8][9][10] Although many studies have been widely carried out, its CO 2 reduction performance is still far from the actual application requirements and the product is mainly CO (2-electron reduction product), [11,12] due to the high recombination rate of charge carriers and low reaction dynamics.
…”
mentioning
confidence: 99%
“…It is observed that the LUMO energy levels of all the M 2+ ions coordinated MOFs are increasing toward more negative side than the pristine Ti‐MOF and the reduction potential of H 2 as well. The more negative shift in the LUMO energy levels favors the enhanced solar light driven photocatalytic H 2 production . Figure b displays the possible mechanism for solar light driven photocatalytic H 2 production activity.…”
Section: Resultsmentioning
confidence: 99%
“…Although g‐C 3 N 4 is well known visible light photocatalyst, in the case of MoS 2 ‐Nap:CB[8]:g‐C 3 N 4 ‐VN, the rate of H 2 evolution was not that high as g‐C 3 N 4 does not act as very efficient electron transport channel in comparison to graphene . Furthermore, for MoS 2 ‐Nap:CB[8]:Graphene‐VN, graphene acts more like an electron channel rather than H 2 evolution site which attributes to its higher activity as compared to the g‐C 3 N 4 ‐VN containing heterostructure …”
Section: Resultsmentioning
confidence: 99%